Predictive Labor Elasticity: Stochastic Demand Modeling in Front-Line Workforce Management - Akash Srivastava (Malikussaleh University, Aceh, Indonesia, 2026)
Labor represents the largest controllable operating cost in retail organizations, yet workforce deployment in many enterprises continues to rely on deterministic scheduling models that are poorly suited to the stochastic demand patterns of modern omnichannel retailing. As customer demand is increasingly distributed across in-store shopping, click-and-collect, curbside pickup, home delivery, and third-party logistics platforms, static labor schedules based on historical averages become ineffective in responding to rapidly changing operational conditions. This article introduces the Probabilistic Labor Elasticity (PLE) framework, an adaptive workforce optimization model that dynamically aligns labor capacity with real-time demand signals through probabilistic forecasting. The proposed framework models customer arrivals using a non-homogeneous Poisson process to generate forward-looking demand estimates and quantify labor elasticity, enabling proactive workforce allocation before demand surges occur. In addition, the framework incorporates Cross-Functional Fluidity, which measures an organization's capability to redeploy employees across operational functions through cross-training, digital enablement, and decentralized decision-making. To further enhance operational responsiveness, the framework integrates AI-powered Mission-Based Task Orchestration, which continuously assigns employees to the highest-value operational tasks during each micro-interval of the business day. The resulting adaptive labor allocation minimizes idle time, reduces service bottlenecks, improves customer responsiveness, and increases operational flexibility compared with conventional scheduling approaches. Furthermore, the study introduces the concept of Marginal Labor Productivity as a quantitative indicator for evaluating the financial value generated through dynamic labor deployment, including avoided labor costs and recovered revenue opportunities. The proposed PLE framework provides retail managers with a scalable decision-support model for improving workforce utilization, operational efficiency, and profitability while supporting resilient, data-driven labor management in increasingly dynamic omnichannel retail environments